Development of a chromatographic lateral flow immunoassay for detection of African swine fever virus antigen in whole blood - Madden, Daniel (Kansas State University, 2021)
African swine fever (ASF) is a highly lethal viral disease of domestic and wild pigs actively circulating in Africa, Europe, and Asia, causing millions of animal deaths and billions of dollars in economic losses. No effective vaccine exists for ASF, which limits control efforts to animal movement restrictions and culling affected herds. Rapid detection of African swine fever virus (ASFV) is essential for disease mitigation, and there is an unmet need for pen-side diagnostic tests with sufficient specificity and sensitivity. Using monoclonal antibodies targeting the ASFV protein p30, we developed a chromatographic lateral flow immunoassay (LFIA) for detection of ASFV in anticoagulated whole blood. The assay is field-deployable, requiring only water and providing results in 25 minutes. The LFIA was capable of detecting a genotype I and a genotype II strain of ASFV in EDTA blood from experimentally-infected pigs at varying time-points after challenge. Diagnostic sensitivity correlated with clinical disease severity, body temperature, and viral DNA levels, and was over 90% in animals with moderate to severe ASF-related symptoms. The LFIA also possessed a robust specificity of 98.7%, an important attribute for a rapid test deployed in outbreak scenarios where false positives and negatives can produce highly disruptive and wide-ranging countermeasures. Additional testing using field samples is required to further assess the viability of the assay as a diagnostic tool.
Keywords: African swine fever; Lateral flow immunoassay; Diagnostics